Long‐Term Nasogastric Versus Percutaneous Endoscopic Gastrostomy Tube Feeding in Older Asians With Dysphagia: A Pragmatic Study. (25th September 2018) - Jaafar, Mohamad Hasif; Mahadeva, Sanjiv; Tan, Kit Mun; Chin, Ai‐Vyrn; Kamaruzzaman, Shahrul B.; Khor, Hui Min; Saedon, Nor Izzati; Tan, Maw Pin
Abstract: Background: A barrier to gastrostomy feeding exists among Asian clinicians and caregivers due to negative perceptions regarding complications. We compared clinical and nutrition outcomes in older dysphagic Asian patients with nasogastric (NG) or gastrostomy tube feeding using a pragmatic study design. Methods: The choice of enteral tube access was determined by managing clinicians and patients/caregivers. Comparisons of tube feeding methods were made during a 4‐month period, adjusting statistically for inherent confounders. Results: A total of 102 participants (NG: n = 52, gastrostomy: n = 50) were recruited over 2 years from 2013 to 2015. Subjects on long‐term NG tube feeding were older (82.67 ± 7.15 years vs 76.88 ± 7.37 years; P < .001) but both groups had similar clinical indications (stroke: 63.5% NG vs 54% gastrostomy; P = .33). After adjustment for confounders, gastrostomy feeding was associated with fewer tube‐related complications (adjusted odds ratio [aOR] = 0.19; 95% confidence interval [CI] = 0.06–0.60) and better complication‐free survival rate (aOR = 0.32; 95% CI = 0.12–0.89) at 4‐month follow‐up. Anthropometric and biochemical nutrition parameters improved significantly in both groups at 4 months, but no significant differences were observed at the end of the study. Conclusion: Gastrostomy feeding is associated with a greater 4‐month complication‐free survival and lower tube‐related complications compared with long‐term NG feeding in older Asians with dysphagia. However, no differences in nutrition outcomes were observed between NG and gastrostomy feeding at 4 months.